Punktkommentarer: Kortlægning af retningslinjer for editionsfaglige kommentarer i digitale, videnskabelige udgaver - Vad, Kirsten; Rasmussen, Krista Stinne Greve; Baunvig, Katrine Frøkjær (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2025)
This article explores the implementation of explanatory commentaries in digital scholarly editions. The authors investigate the methodologies used in these digital editions, comparing their guidelines in order to identify similarities and differences. Additionally, they examine more recent printed scholarly editions to determine if their guidelines diverge significantly from those of digital editions. Spanning editions published from the 1990s to the 2020s, this study evaluates whether temporal shifts are reflected in commentary guidelines and approaches. The research includes a comparative analysis of digital scholarly editions from Den-mark, Norway, Sweden and Finland, featuring works by authors such as Georg Brandes, N.F.S. Grundtvig, Henrik Ibsen, Ludvig Holberg, Selma Lagerlöf, Søren Kierkegaard and Zacharias Topelius. These editions demonstrate a variety of practices and priorities in commentary, influenced by the intended readership, commentary thresholds and the integration of historical, mythological or biographical content. The authors conclude by emphasising the need for accessible guidelines to support future scholarly editions. They also suggest that emerging technologies, such as artificial intelligence, could advance digital commentary practices further.